The Effect Of Compensation On Job Satisfaction Of Employees Of PT. Rian Putra Mandiri Majalengka - Wulan Ariani Damayanti; Rika Kartika (SINTESA, 2022)
This study aims to determine employee compensation and job satisfaction and to determine the effect of compensation on employee job satisfaction at PT. Rian Putra Mandiri Majalengka. This study uses survey methods, data collection techniques used are observation methods, questionnaires and data processing related to the problems studied, namely employee compensation and job satisfaction. The analysis technique used is simple regression analysis, Product Moment correlation test, coefficient of determination and hypothesis testing. The results of the discussion regarding X (Compensation) are 1761 (Very Good) as a whole which is assessed based on the indicators because it is in the 1680 - 2000 interval, and regarding Y (Employee job satisfaction) is 1806 (Very Good) overall which is assessed based on the following indicators. the indicator is because it is in the interval 1680 – 2000. The relationship between compensation and job satisfaction of employees of PT. Rian Putra Mandiri Majalengka is 0.252 or 25.2%. This shows that compensation has a fairly strong influence on employee job satisfaction. While the remaining 74.8% is influenced by other factors. The hypothesis which states that there is a positive influence between compensation for employee job satisfaction at PT. Rian Putra Mandiri Majalengka and can be accepted with tcount > ttable or 3.582 > 2.02108, meaning Ho is rejected or H1 is accepted. Rian Putra Mandiri Majalengka, this will be useful in increasing employee job satisfaction and increasing the quality and quantity of employee work.